The effect of sponsorship disclosure on consumers perception of source credibility and the likelihood to recommend organic hair care products - Dube, Priscilla Fungai (Marketing, 2022)
Influencer marketing has made its way to the forefront of online marketing due to the rapid expansion and usage of social media platforms. Despite the increased adoption of influencer marketing, the effect of sponsorship disclosure on source credibility remains under-researched in academia. This study aimed to address this research gap in two parts. Firstly, by evaluating the characteristics and significance of social media influencers. Secondly, by investigating the effect of sponsorship disclosure on consumers perception of source credibility and the likelihood to recommend organic hair care products. The selected social media platform for this study was Instagram, due to its growing popularity and increased usage by influencers. The hair care retail business as a proven multi-billion dollar industry, set itself as a valuable industry for the purposes of this study. The research methodology involved the collection of primary data from existing literature on influencer marketing strategies and social media influencers. Ohanian's Source Credibility model was found to be of relevance to the research objectives, therefore, it was used a theoretical framework for the study. Secondary data was collected by exploring the relationships between sponsorship disclosure, source credibility and electronic word-of-mouth marketing. Quantitative data was collected through a structured questionnaire which was issued online to University of Cape Town students. To ensure that the research contributed to existing academic literature, the target population chosen for the study was the Generation Z. The data collected was analysed using inferential statistical methods in order to test the hypotheses. A structural equation model was used to analyse the relationship between variables and the results indicated that all hypotheses were found to be supported, depicting that sponsorship disclosure has an impact on perceived source credibility. Additionally, the results indicated that respondents were more likely to participate in word-of-mouth recommendations for products endorsed by influencers that they regarded to be credible. The overall research findings provide valuable insights on consumer perception towards the credibility of social media influencers. This information can be used in marketing practice to aid marketers to develop appropriate strategies for sponsored influencer marketing campaigns. Furthermore, this study contributes to academia by adding empirical data to the existing body of literature on influencer marketing.